2018
DOI: 10.1177/1066480718795500
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol and Substance Use on a Couple System

Abstract: This case study aims to analyze the effects of alcohol and substance use on a couple system. An African American, heterosexual couple was selected for analysis due to dual alcohol and substance use negatively impacting their relationship in addition to generalized anxiety and major depressive disorder. The reliance of alcohol and substance use to cope with relational stressors and mental health systems was detrimental to the relationship. The clients initially presented with trust issues stemming from infideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In terms of clinical implications, various forms of therapy and therapeutic techniques could be utilized to aid in the treatment of this population. Prior research has shown that coping with alcohol and substance use may be treated with cognitive behavioral therapy intervention, for example, by altering negative core beliefs (Brotchie et al, 2004; Molla et al, 2018). Further, couples and/or family therapy could be helpful as treating alcohol and substance use concerns relationally may uncover patterns contributing to usage (Molla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of clinical implications, various forms of therapy and therapeutic techniques could be utilized to aid in the treatment of this population. Prior research has shown that coping with alcohol and substance use may be treated with cognitive behavioral therapy intervention, for example, by altering negative core beliefs (Brotchie et al, 2004; Molla et al, 2018). Further, couples and/or family therapy could be helpful as treating alcohol and substance use concerns relationally may uncover patterns contributing to usage (Molla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that coping with alcohol and substance use may be treated with cognitive behavioral therapy intervention, for example, by altering negative core beliefs (Brotchie et al, 2004; Molla et al, 2018). Further, couples and/or family therapy could be helpful as treating alcohol and substance use concerns relationally may uncover patterns contributing to usage (Molla et al, 2018). Alcohol use concerns across Hispanic individuals have been found to be linked to citizen status (Caetano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%